A citizen-soldier of the Roman Republic: Beyond the literary creation - Faszcza, Michał Norbert (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2021)
The main aim of the article is to draw attention to the distortion of Republican Roman soldiers’ image. Some modern scholars treat the ‘ideal type’ as a reflection of reality and attribute to legionaries the features desired by representatives of the social elite. Meanwhile, it seems that less wealthy citizens created their own vision of the qualities that a Roman soldier should have. This leads to the question of whether the officers and their subordinates had the same understanding of obedience and discipline.